Pelatihan Pembentukan Bonsai Tanaman Beringin Pada Forum Remaja Masjid Jami’ Di Dusun Taman Kulon Rt. 001/002 Kecamatan Tirtomoyo Kabupaten Wonogiri: shaping of banyan plants bonsai - ahmad rosyid; Suwarto; Agus Purwanto (Universitas Mataram, 2022)
: Training on the shaping of banyan plants bonsai for the youth of Jami’ Mosque, Taman Kulon RT.001002, Wiroko Village, Tirtomoyo District, Wonogiri Regency. Team : Ahamad Rosyid, M.Pd.I, Prof. Dr. Suwarto, M.Pd dan Drs. Agus Purwanto, M.Pd. The purpose of this service is to give training and experience to youth members of Masjid Jami’ in Taman Kulon RT.001002, Wiroko Village, Tirtomoy District, Wonogiri Regency during the Covid – 19 pandemic. Methode that is used in this service is a discoursing and mentoring method. The material presented is the shaping bonsai on banyan plants. Discoursing focused on counseling and training was carried out during the practice of shaping banyan plant bonsai until monitoring the development of these banyan plant bonsai. The expected target from the counseling and training is an increase in understanding of the way to shape banyan plants bonsai by at least 20% among members of the Jami’ Mosque Youth Forum in Taman Kulon RT.001002, Wiroko Village, Tirtomoy District, Wonogiri Regency. The analysis of pre-test and post-test data showed that there was an increase in understanding among Jami’ Mosque Youth Forum in the shaping of bonsai on banyan plants from an average score of 18 to 29 or an increase in understanding of 66%. In addition, it is also proven by the shape of the leaves on the banyan plants which are getting smaller, so it can be concluded that counseling and training on the shaping of banyan bonsai can be said to be successful.